2017
DOI: 10.1538/expanim.16-0078
|View full text |Cite
|
Sign up to set email alerts
|

Morphological features of coronary plaques in WHHLMI rabbits (<i>Oryctolagus cuniculus</i>), an animal model for familial hypercholesterolemia

Abstract: Abstract:In order to examine their suitability for studies on coronary atherosclerosis, we evaluated the features of coronary atherosclerotic plaques in myocardial infarction-prone Watanabe heritable hyperlipidemic (WHHLMI) rabbits, a spontaneous animal model for coronary atherosclerosis and myocardial infarction. Coronary segments of the hearts of 187 WHHLMI rabbits (10-29 months old) were sectioned serially and stained histopathologically and immunohistologically. Progression of coronary lesions was prominen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…In the early stages of atherosclerosis, macrophages infiltrate into the arterial intima from the surface of the intima and the vasa vasorum in the deep intima. In WHHLMI rabbits, the vasa vasorum was observed with extracellular lipid deposits and macrophage accumulation in the deep area of advanced coronary lesions, in addition to the intimal surface 29) . Therefore, it should be noted that the pathogenesis of ath- Table 3.…”
Section: Contribution Of Whhl Rabbits To Studies Of Atherogenesismentioning
confidence: 95%
See 3 more Smart Citations
“…In the early stages of atherosclerosis, macrophages infiltrate into the arterial intima from the surface of the intima and the vasa vasorum in the deep intima. In WHHLMI rabbits, the vasa vasorum was observed with extracellular lipid deposits and macrophage accumulation in the deep area of advanced coronary lesions, in addition to the intimal surface 29) . Therefore, it should be noted that the pathogenesis of ath- Table 3.…”
Section: Contribution Of Whhl Rabbits To Studies Of Atherogenesismentioning
confidence: 95%
“…Therefore, it should be noted that the pathogenesis of ath- Table 3. Characteristics of coronary lesions elucidated in studies using WHHL rabbit family • Differences between coronary artery lesions rich in fibers and aortic lesions rich in lipids 15,61) • The relevance of factors other than conventional risk factors (such as serum total cholesterol levels, HDL levels, oxidative stress, hyperglycemia, hypertension, and others) in the development and progression of coronary lesions 75) • Involvement of genetic factors different from aortic lesions in the development of coronary artery lesions 75) , and involvement of the coronary curvature in the progression and composition of lesions 68) • The relevance of additional factor(s) in the rupture of unstable coronary lesions characterized by thin-capped fibroatheroma 4,22,65) • Involvement of coronary spasm in rupture of coronary lesions and the occurrence of acute coronary syndromes 22,65) • The relevance of several serum lipid molecules identified with lipidome analyses in the development and progression of coronary lesions 75) • Involvement of macrophages infiltrated into the deep area of intima through vasa vasorum 29) in coronary outward remodeling 67) • Suppression and destabilization of atherosclerotic lesions by lowering serum lipid levels 5) human coronary lesions 30) , various types of coronary lesions were observed in WHHLMI rabbits (Fig. 3), such as fatty streak, fibrous lesion, fibroatheroma, thin-capped fibroatheroma, and advanced complicated lesions with reduced cellular components, calcification, vasa vasorum, etc.…”
Section: Contribution Of Whhl Rabbits To Studies Of Atherogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that other factors than serum cholesterol levels may be related to the progression and composition of coronary lesions in WHHLMI rabbits 9 ) . The WHHLMI rabbit is an animal model for human familial hypercholesterolemia 10 ) and develops diffuse coronary lesions 9 , 11 ) even with normal chow feeding. The factors responsible for individual differences in the development of coronary lesions have yet to be identified.…”
Section: Introductionmentioning
confidence: 99%